Application of Inquiry Learning Model with Lesson Study (LS) Pattern on Student Learning Outcomes in Colloid System Material - Nur H. Wahyuni; Suherman Suherman; Tahril Tahril (Jurnal Akademika Kimia, 2021)
This study aimed to know the effect of applying the inquiry learning model with lesson study (LS) pattern on student learning outcomes in colloid system material in class XI SMA Negeri 1 Sigi. This type of research was a quasi-experiment with an equivalent post-test design. Samples were determined by the purposive sampling method. The sample used in this study was students of class XI MIA 3 as an experimental class with 24 students and XI MIA 4 students as a control class with 20 students. The processing of student learning outcomes data used a non-parametric analysis of the Mann-Whitney U-Test test. The results showed that the mean value of the experimental class was higher than the control class, which was 23.98>15.82. Results of statistical analysis sig. 2-tailed was (0.019) <0.05 and Zcalculation (-2.336) < Ztable (-1.96), based on decision-making criteria, it stated if the value of -Zcalculation<Ztable then H0 is rejected. Therefore, it can be concluded that there is the effect of applying the inquiry learning model with lesson study (LS) pattern on student learning outcomes in colloid system material in class XI SMA Negeri 1 Sigi.